Analysis of Moral Values in Jojo Rabbit Movie - Muhammad Irvan Syawal; Bukhari Daud; Iskandar Abdul Samad (Research in English and Education Journal, 2021)
This research is a literary study on moral values found in “Jojo Rabbit” movie. A descriptive qualitative was undertaken to investigate the research question in this study. Kinnier’s theory (2000) was used to analyze the data related to the types of moral values of the movie. The subject of this research is “Jojo Rabbit” movie and the moral values are the objects. The results of the study showed that there are three of the four types of moral values found in “Jojo Rabbit” movie, namely ”commitment to something that greater than oneself”; “self-respect with humility, self-discipline, and acceptance of personal responsibility”; and “respect and caring the other”.The most frequent type of moral values used in the movie is “respect and caring the other”.